PENGARUH TANIN-FORMALDEHIDA TERHADAP SIFAT FISIK DAN KETAHANAN TARIK PAPAN SERAT YANG DIBUAT DENGAN PROSES BASAH - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Condensed-tannin from bark of Pinus merkusii Jungh et de Vriese, can react with formaldehyde in alkali or acid condition to form tannin-formaldehyde. The reaction product is assumed to be an excellent sizing material for fiberboard manufactures. The purpose of this research is to study the effect of tannin-formaldehyde sizing on moisture content, density, thickness, water absorption, thickness swelling, and tensile strength parallel to surface of fiber board properties. The amount of tannin-formaldehyde added to pulp consisting of 0,3,6, 9 and 1.2 percent based on oven dry pulp. Results indicate that the addition of tannin-formaldehyde during the fiberboard making process has a highly significant effect on reducing water absorption and thickness swelling. Similarly, the tensile strength parallel to surface of fiberboard was significantly improved by adding tannin-formaldehyde. Overall improvement of fiberboard properties could be achieved by adding 12 percent of the sizing agent to the stock.